Development of Islamic Family Law Thought Regarding Legal Norms of Waris, Wasiat and Hibah. - Irfan Abdurahman; Asep Lukman Daris Salam; Erfan Shofari Sholahuddin (al-Afkar, Journal For Islamic Studies, 2024)
Discussion of shari'ah which is a reference to divine decrees as "standard operational procedures" and fiqh which is a sub-foundation of shari'ah in the form of interpretation at the next level as a product of anthropological subjectivity, requires the formulation of rules so that the product of legal understanding does not go off the rails of shari' at. Meanwhile, the idea of renewing the rules of fiqh, which leads to changes in the formulation of the main rules of fiqh, will give rise to methodological problems which are feared to deconstruct the established formulation. The main objective of Islamic law is to realize the ideals of human benefit which are based on the values of social justice as God's creatures. The ideals of Islamic social justice at the level of implementation are reflected in the juridical-normative provisions in both the Qur'an and al-Hadith, the basis of which are the values of equality (al-musawah), justice (al-'ilah) and freedom ( al-hurriyah). Islamic Sharia is a concept of religious teachings that regulates all dimensions of human life. Thus, Islamic law is a comprehensive concept of life. However, the legal provisions in both the Qur'an and al-Hadith are mostly stated in common language (mujmal) so that they require ijtihad. Therefore, it is very possible or even inevitable that there will be a diversity of interpretations of religious texts.